Upaya Guru Mengatasi Kesulitan Belajar Disleksia pada Siswa Kelas Atas di Sekolah Dasar Negeri 15 Kartiasa - Zuri Astari (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
Dyslexia is a learning difficulty characterized by an inability to read, including spelling and writing. This research aims to identify students who experience learning challenges with dyslexia and find out teachers' efforts in dealing with upper-class students who share dyslexia. Researchers used a qualitative approach and descriptive research type. Primary data sources are class teachers and dyslexic students. Meanwhile, secondary data sources are complementary data in the form of student learning outcomes, student attendance, and teacher notes. Data collection techniques use interviews, observation, and documentation. The data analysis techniques are data reduction, data display, and verification. The research results show that six students in the SD Negeri 15 Kartiasa upper classes experienced dyslexia. Three of the six students fall into the severe dyslexia category, namely having difficulty spelling, reading, and speaking clearly. In comparison, the other three students fall into the mild dyslexia category: inability to read fluently. Efforts have been made to overcome dyslexic students. Namely, teachers provide exceptional guidance to practice reading words and sentences with additional time outside of class hours, fostering motivation so dyslexic students are enthusiastic about learning to read. Teachers also use varied and fun learning methods so dyslexic students can understand learning. It is hoped that with this research, the school will be more optimal in overcoming learning difficulties, such as creating unique programs for dyslexic students and providing facilities such as supporting books for dyslexic students.